THEORETICAL BASIS OF IMPROVING ENVIRONMENTAL EDUCATION IN PRIMARY STUDENTS WITHIN THE CONTEXT OF INTERDISCIPLINARY INTEGRATION - Jurakul Panjiyev (Journals Park Publishing, 2025)
This article discusses the theoretical and pedagogical foundations of effective organization of environmental education among primary school students, teaching them to consciously approach environmental protection, as well as improving this process based on interdisciplinary integration.
Keywords: Environmental education, interdisciplinary integration, primary school, environmental culture, educational content.